Incidence of phlebitis associated with the use of peripheral IV catheter and following catheter removal - Janete de Souza Urbanetto; Cibelle Grassmann Peixoto; Tássia Amanda May
ABSTRACT Objective: to investigate the incidence of phlebitis and its association with risk factors when using peripheral IV catheters (PIC) and following their removal - (post-infusion phlebitis) in hospitalized adults. Method: a cohort study of 171 patients using PIC, totaling 361 punctures. Sociodemographic variables and variables associated with the catheter were collected. Descriptive and analytical statistical analyses were performed. Results: average patient age was 56.96 and 51.5% of the sample population was male. The incidence of phlebitis was 1.25% while using PIC, and 1.38% post-infusion. The incidence of phlebitis while using PIC was associated with the length of time the catheter remained in place, whereas post-infusion phlebitis was associated with puncture in the forearm. Ceftriaxone, Clarithromycin and Oxacillin are associated with post-infusion phlebitis. Conclusions: this study made it possible to investigate the association between risk factors and phlebitis during catheter use and following its removal. The frequency of post-infusion phlebitis was larger than the incidence of phlebitis with the catheter in place, with Phlebitis Grade III and II being the most frequently found in each of these situations, respectively. Aspects related to post-infusion phlebitis can be explained, given the limited number of studies addressing this theme from this perspective.